2022
DOI: 10.2147/ijgm.s374777
|View full text |Cite
|
Sign up to set email alerts
|

Development of Risk Prediction Model for Muscular Calf Vein Thrombosis with Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Purpose This study aims to establish a risk prediction model for muscular calf vein thrombosis (MCVT) in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Methods The research sample consisted of 248 patients with AECOPD and all of them underwent vascular ultrasounds of both lower limbs in this retrospective study. Univariate analysis and multivariate logistic regression analysis were conducted on factors with significant group differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Underlying conditions such as malignant tumors, varicose veins, renal failure, and heart failure, along with highrisk factors like anticancer radiotherapy, chemotherapy, oral contraceptives, hormone replacement therapy, obesity, and smoking, can elevate the prevalence of MCVT [18,19]. MCVT often goes unnoticed due to mild and non-acute symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying conditions such as malignant tumors, varicose veins, renal failure, and heart failure, along with highrisk factors like anticancer radiotherapy, chemotherapy, oral contraceptives, hormone replacement therapy, obesity, and smoking, can elevate the prevalence of MCVT [18,19]. MCVT often goes unnoticed due to mild and non-acute symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other veins in the lower extremity, the veins in the calf muscles are more likely to develop thrombosis due to their extensive branches, small diameters, thin walls, few venous valves, and slow blood ow [2]. A previous study reported that in certain populations up to 91% of patients with DVT could have CMVT [3]. Although CMVT gradually disappears in most cases, there is a proportion of cases where CMVT progresses to DVT [4] or even pulmonary embolism (PE) [5, 6].…”
mentioning
confidence: 99%